PERLINDUNGAN HAK KEPEMILIKAN TANAH MASYARAKAT DESA PAKEL: PENELUSURAN LEGAL STANDING AKTA 1929 DALAM SENGKETA TANAH DENGAN PT. BUMI SARI - Irischa Aulia Pancarani (Program Studi Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2023)
This study aims to identify the legal position of the 1929 deed in the application for land rights and the legal protection of land rights for the Pakel village community against land ownership by PT. Sari Earth. The research method is library law research with a normative juridical approach and support from qualitative analysis. According to the research's findings, 800 families in the Pakel village community were the owners of the 1929 deed, which recognized the land clearing rights (Ontginningsrecht) as the foundation for applying for land conversion and registration. The granting of communal property rights was based on nearly a century of uninterrupted co-cultivation. This document can serve as proof of title and an initial guide for submitting applications for land registration to residents, especially for the portion of land claimed since 1985 by PT. Bumi Sari as part of the company's Cultivation Rights (HGU) concession. The Pakel community can protect their rights by filing civil lawsuits and state administration lawsuits. In addition, non-litigation efforts such as mediation, forming a special team, and providing appropriate compensation or relocation can also be carried out.